Brand image co-creation and individual identity extension in online environments: a Facebook investigation - Rosenthal, Benjamin (2014)
In this thesis I investigate the extent to which companies can build a more communal environment out of their fan pages while also evaluating the corresponding brand value that may come from having such a communal environment. My research is comprised in three articles: in the first article, I describe how the brand image is created or augmented in the fan page environment, therefore providing demonstrable evidence of value creation. In the second article, I describe how individuals use fan page semiotic elements to communicate their identities. Finally, in the third article, I describe the possible communal characteristics of a fan page and the conditions that enable it to evolve to the virtual brand community concept. As a result, I will contribute to the marketing literature on the use of Facebook for communicating brand identity, on the co-creation of the brand image in social media context, and on the conceptual definition of fan pages as a communal environment.